(3GdeMGSHI GdOhdjI eY GdJWHjb GdYedj ddeMGSHI GdOhdjI (B/s - (3LQHhY, jhSa eMeOs; (3MdS, SGde YHO Gddg s ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2002)
(3eaghe GdeMGSHI GdOhdjI,GdTQcGJ hGdeDSSGJ GdeMdjI hGdEbdjejI hGdOhdjI, GdJLGQI GdEdcJQhfjI hGdYhdeI, eYGjjQ GdeMGSHj GdOhdj Qbe(B1(3, GdeYjGQ GdeMGSHj GdOhdj Qbe (B2 (3,GdeYjGQ GdeMGSHj GdOhdj Qbe (B4(3, GdeYjGQ GdeMGSHj GdOhdj Qbe (B7(3, GdeYjGQ GdeMGSHj Qbe (B8(3, GdeYjGQ GdeMGSHj Qbe (B9(3, MJi GdeYjGQ GdeMGSHj Qbe (B37(3, GdeYGdLI GdeMGSHjI dJcGdja GdHjFI, GdeTGcd GdeMGSHjI ddTQcGJ GdOhdjIs
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs